1996
DOI: 10.1016/0014-5793(96)00478-4
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitor protein of phosphorylated nitrate reductase from spinach (Spinacia oleracea) leaves is a 14‐3‐3 protein

Abstract: The inhibitor protein (IP) that inactivates spinach leaf N ADH:nitrate reductase (NR) has been identified for the first time as a member of the eukaryotic 14-3-3 protein family based on three lines of evidence. First, the sequence of an eight amino acid tryptic peptide, obtained from immunopurified IP, matched that of a highly conserved region of the 14-3-3 proteins. Second, an authentic member of the 14-3-3 family, recombinant Arabidopsis GFI4¢o, caused inactivation of phospho-NR in a magnesium-dependent mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
120
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(125 citation statements)
references
References 32 publications
4
120
0
1
Order By: Relevance
“…Osmotic stress inactivates NR (Kaiser and Föster, 1989), but a simple phosphorylation-dephosphorylation cycle is not sufficient to explain the control of NR. The inactivation of NR occurs by the phosphorylation of serine-543 (Douglas et al, 1995;Su et al, 1996) which is catalyzed by a calcium-dependent (calmodulin-domain) protein kinase (CDPK) or SNF1-related protein kinase (Bachmann et al, 1996a;Douglas et al, 1997;Douglas et al, 1998), followed by binding of phosphorylated NR to an NR inhibitor protein (NIP) made up of one or more 14-3-3 proteins (Bachmann et al, 1996b;Moorhead et al, 1996) which bind directly to the phosphorylation site of NR. While many proteins have been found to bind to 14-3-3 proteins, plant NR was the first in which a functional 14-3-3s effect (inhibition of phosphorylated NR) was identified in a physiological setting (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Osmotic stress inactivates NR (Kaiser and Föster, 1989), but a simple phosphorylation-dephosphorylation cycle is not sufficient to explain the control of NR. The inactivation of NR occurs by the phosphorylation of serine-543 (Douglas et al, 1995;Su et al, 1996) which is catalyzed by a calcium-dependent (calmodulin-domain) protein kinase (CDPK) or SNF1-related protein kinase (Bachmann et al, 1996a;Douglas et al, 1997;Douglas et al, 1998), followed by binding of phosphorylated NR to an NR inhibitor protein (NIP) made up of one or more 14-3-3 proteins (Bachmann et al, 1996b;Moorhead et al, 1996) which bind directly to the phosphorylation site of NR. While many proteins have been found to bind to 14-3-3 proteins, plant NR was the first in which a functional 14-3-3s effect (inhibition of phosphorylated NR) was identified in a physiological setting (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Although effects of 14-3-3 protein on enzyme activities in many cases have been difficult to ascertain, one general function of 14-3-3 proteins may be to serve as direct modulators of enzyme activity (5,6). 14-3-3 proteins either inhibit or activate their targets; they inhibit nitrate reductase (7,8) and myosin II heavy-chain-specific protein kinase C (9) and activate proteins such as tyrosine and tryptophan hydroxylases (10), exoenzyme S (11), the glucocorticoid receptor (12), Raf-1 kinase (13,14), the DNA-binding transcription factor p53 (15), and the plasma membrane H ϩ -ATPase (16). The generally accepted paradigm is that the interaction between the 14-3-3 protein and its target is inducible.…”
mentioning
confidence: 99%
“…In fact, from animal research, it is known that a common property of 14-3-3 proteins is the capability to associate with interacting proteins (5,6). Recently, it has been demonstrated that a similar mechanism of regulation occurs also for NADH:nitrate reductase from spinach leaves (7,8). Nitrate reductase activity is inhibited upon binding of endogenous 14-3-3 proteins, which can occur only after the enzyme has been phosphorylated at a specific serine residue by a calcium-dependent protein kinase (9).…”
mentioning
confidence: 99%
“…Nitrate reductase activity is inhibited upon binding of endogenous 14-3-3 proteins, which can occur only after the enzyme has been phosphorylated at a specific serine residue by a calcium-dependent protein kinase (9). It has also been shown that these endogenous 14-3-3 proteins are a mixture of different 14-3-3 homologs (7) and that multiple 14-3-3 isoforms are able to inhibit nitrate reductase in vitro (10). The phosphorylated motif of the nitrate reductase involved in the interaction has been identified, and it is similar to consensus sequences for 14-3-3 binding, occurring in most animal 14-3-3-interacting proteins (10).…”
mentioning
confidence: 99%